Computer Simulation of the Thin Film’s Growth Process during Thermal Vacuum Evaporation - T. Su. Chu (Известия высших учебных заведений России: Радиоэлектроника)
The various thin film growth mechanisms during thermal vacuum evaporation at atomic level are considered under different condition. Which factors and how influence on the quality of obtained thin films was demonstrated. The thin film’s growth process in intermediately (Stranski-Krastanov) mode was simulated based on Monte Carlo method for determination of active particles’ number, and quasi-Newtonian lattice method for determination of optimal direction of particles’ motion. On this model in any given conditions the fractal growth process was analyzed. The phenomenon (opportunity) of the control and management of the growth process of thin films was considered.